Responses to selection for yield traits and key diseases among common bean genetic pyramids across locations - Okii, Dennis; Badji, Arfang; Odong, Thomas; Talwana, Herbert; Tukamuhabwa, Phinehas; Magdalena, William; Gepts, Paul; Mukankusi, Clare (Journal of Crop Improvement, 2019)
Knowledge of response to selection (R) helps to analyze the efficiency of crop-improvement programs and devise appropriate selection strategies. The objective of this study was to determine response to selection of common bean (Phaseolus vulgaris L.) genetic pyramids for diseases and yield traits. Populations evaluated included pyramided parents, climbing pyramided progenies, and checks. The trial was planted in 2016 in Uganda (Kabale and Kawanda) and Northern-Tanzania (Maruku and Kitengule) in randomized incomplete blocks with three replications. Summarized data and appropriate parameters were incorporated into the breeder’s equation (R = ih2S). R was positive for mean days to flowering (5 days) and negative for mean number of pods per plant (−9.5 pods) and 100-seed weight (−1.9 g). Diseases (anthracnose, angular leaf spot, and bean common mosaic virus) had positive, undesirable R. Generally, pyramided lines segregated at BC3F9 for disease resistance and yield traits, and thus, superior bean lines should be identified in subsequent generations, such as BC3F11.
Keywords: Breeder’s equation; Crop-improvement; Gene pyramiding; Genetic variation; Selection